Child Adoption According to Customary Law In Desa Pemo Kecamatan Kelimutu Kabupaten Ende - Sumirahayu Sulaiman; Kosmas Minggu; Sakura Alfonsus (IHSA Institute, 2022)
The execution of chil adoption in Indonesia each district one differing from other district since done legalistic of custom going into effect in pertinent district. One of thet district is ini Desa Pemo. Thought of generally in java with society which have system of familiarity patrilineal with system of child adoption done do not bodly and do not in cash,however in this didtrich is child adoption conducted by bold and cash. This research target is to know execution of child adoption in endowment is Desa Pemo and to know legal consequences of child adoption in endowment in Desa Pemo. Used by research method is method qualitative since in this research depicted by an event as things have panned out, that is hit execution of child lifting and domicile foster child of acocoding to customary low in Desa Pemo. This research use method of empirical apporoach yuridis that is aim to comperehend that law is do not solely as an a set the legislation order having the character of mere normatif, however law comperehended by as society behavior wihich symptom in life socialize, always have the interaction and relate to social aspect. Pursuant to research result earn taken by a conclucion that is child adoption in Desa Pemo executed boldly and the chas that is done according to customary law in Kabupaten Ende well-held almost always in klan of hand in glove big family according to line of familiarity patrilineal